Duration of Firms: The Role of Financial Considerations in Peruvian Manufacturing Firms - Tolentino Raymond, Edinson (2021)
This article is a summarized version of the research "Duration of companies: the role of financial considerations in Peruvian manufacturing companies", carried out within the framework of the CIES 2019 Annual Research Contest, which is sponsored by the Ministry of Economy and Finance (MEF), the Manuel J. Bustamante de la Fuente Foundation and the Ministry of Energy and Mines (MINEM).